Exploring local friendliness, perceived discrimination, and brand love’s mediation on tourist behavior in Tangkahan, North Sumatra - Erina Alimin; Ali Syah Putra; Nasib Nasib; Siti Alhamra Salqaura; Debora Tambunan (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
This study explores the impact of local hospitality and perceived discrimination on tourist behavior, with brand love as a mediating variable, in the context of Tangkahan tourist attractions in North Sumatra. We collected data from a survey of 237 tourists visiting Tangkahan and analyzed it using Structural Equation Modeling (SEM). The analysis shows that local friendliness positively and significantly affects brand love. In contrast, perceived discrimination has no significant effect on brand love. In addition, local friendliness also has a positive and significant effect on tourist behavior, while perceived discrimination has no significant impact on tourist behavior. Furthermore, brand love has a positive and significant influence on tourist behavior. Brand love indirectly mediates the relationship between local friendliness and tourist behavior. However, brand love does not significantly mediate the relationship between perceived discrimination and tourist behavior. The practical implications of this study suggest the need for a more holistic strategy to improve the tourism experience, including addressing discrimination and strengthening the positive elements that influence brand love.